Post-discharge outcomes associated with bronchopulmonary dysplasia in extremely low birth weight infants: A retrospective chart review study. - Thomas Mathen Maveli (17046295) (2023)
Objective Bronchopulmonary dysplasia (BPD) is a chronic lung disease that commonly affects premature infants, especially those born before 28 weeks of gestation. Infants with BPD are at risk for various health problems This study aimed to compare the health outcomes of infants with BPD at 18 months of age. Design A retrospective chart review study of the post-hospital discharge outcomes of infants with BPD. Electronic charts of all preterm infants born less than 28 weeks gestation and admitted to the WWRC Hospital from January 2017 until December, 2019. Methods We collected basic demographic variables of all the newborns borns less than 28 weeks gestation and mothers born at WWRC. Only infants with any type of BPD included in the analysis. We compared health outcome variables of infants with mild BPD to infants with moderate to severe (MS) BPD form NICU discharge to 18 moths of age. Health outcome variables included types of respiratory support, respiratory infection, other chronic illnesses, chronic medication use and growth and neurodevelopmental impairment. The Data was retrospectively analyzed after chart review. Data set was analyzed accordingly vis SPSS software version 29. Results: Of the total 177 infants , 89 infants had mild BPD and 88 infants had MS-BPD. compared with infants mild-BPD, MS-BPD were mostly male (70% vs 42, p<0.001), had a lower birthweight (799 vs 896 grams, p <0.001), lower gestational age remained 25.3 vs 25.8 weeks, p=0.002, higher intubation rate (87% vs 67%, p=0.001) and surfactant administration in the delivery room for (70% vs 50%, p=0.007). Infants with mild-BPD, discharged before 36 weeks was 38 vs 0%, p<0.001). NICU hospitalization beyond 50 weeks in infants with MS-BPD was 16% vs 0%, p<0.001. Twelve Infants with BPD was discharged home on oxygen was (14%) vs 0%, p<0.001). Infants in the MS-BPD group had a higher incidence of post discharge pulmonary hypertension (13.6% vs 1.1%, p=0.001, more often on inhaled steroids group was 42.2% vs 18.8%, p=0.001. PDA surgery was done in 10(11%) infants with MS-BPD vs 2(2%) infants with mild-BPD, p=0.017). Sleep study was required more in MS BPD cases (15% vs 1%, p=0.001). Out of the 13 infants with MS-BPD, the sleep study showed 8 (9%) infants with apnea and 3(3.4%) with hypoxia (p=0.003). Speech delay was noticed in 30% of infants with MS-BPD vs 23% in infants with mild-BPD (p=0.29). Gross motor developmental delay was higher in MS-BPD ( 26% vs 11%, p=0.011). Conclusions The study provides valuable insights into the post-discharge outcomes of infants with BPD. The results highlight that infants with moderate to severe (MS) BPD have poorer outcomes compared to those with mild BPD. These findings emphasize the need for careful monitoring and follow-up care for infants with BPD, particularly those with MS-BPD. The results of this study can be used to develop targeted interventions aimed at improving the long-term outcomes of infants with BPD.